2013
DOI: 10.1111/gcb.12121
|View full text |Cite
|
Sign up to set email alerts
|

Radiation budget changes with dry forest clearing in temperate Argentina

Abstract: Land cover changes may affect climate and the energy balance of the Earth through their influence on the greenhouse gas composition of the atmosphere (biogeochemical effects) but also through shifts in the physical properties of the land surface (biophysical effects). We explored how the radiation budget changes following the replacement of temperate dry forests by crops in central semiarid Argentina and quantified the biophysical radiative forcing of this transformation. For this purpose, we computed the albe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 75 publications
3
50
0
6
Order By: Relevance
“…In temperate Argentina, Houspanossian et al (2013) found that the replacement of dry forests by crops resulted in an increase of albedo but still forests exhibited cooler canopies than croplands. The cooler canopies were a result of a higher aerodynamic conductance that enhanced the capacity of tree canopies to dissipate heat into the atmosphere and to both latent and sensible heat fluxes operating simultaneously to cool forest canopies.…”
Section: Drivers Of Local Differences Between Different Land Cover Typesmentioning
confidence: 99%
“…In temperate Argentina, Houspanossian et al (2013) found that the replacement of dry forests by crops resulted in an increase of albedo but still forests exhibited cooler canopies than croplands. The cooler canopies were a result of a higher aerodynamic conductance that enhanced the capacity of tree canopies to dissipate heat into the atmosphere and to both latent and sensible heat fluxes operating simultaneously to cool forest canopies.…”
Section: Drivers Of Local Differences Between Different Land Cover Typesmentioning
confidence: 99%
“…Existen evidencias de que los cambios en la cobertura de la vegetación pueden modificar las condiciones climáticas a escala local, regional y global (Adams 2007;Lee et al 2011;Anderson-Teixeira et al 2012;Houspanossian et al 2013;Flerchinger et al 2015). A su vez, pueden tener efectos sobre la interfaz broza-suelo donde se produce la descomposición (Eviner and Chapin 2003;Yates et al 2000;Schiling et al 2016 o similares).…”
Section: D��������unclassified
“…A su vez, pueden tener efectos sobre la interfaz broza-suelo donde se produce la descomposición (Eviner and Chapin 2003;Yates et al 2000;Schiling et al 2016 o similares). En las configuraciones vegetales analizadas durante los años estudiados (2009)(2010)(2011), la mayor temperatura del aire observada en el arbustal mixto cerrado y los bosques puede deberse a que el menor albedo que poseerían (Lee et al 2011;AndersonTeixeira 2012) no se vea compensado por su mayor rugosidad (y su mayor disipación de calor latente), como podría esperarse en base a estudios previos (Houspanossian et al 2013). A su vez, una mayor temperatura podría deberse a que en arbustales y bosques existe una mayor superficie oscura de troncos, ramas y broza sobre el suelo, que podría retener calor incluso durante la noche, cuando el efecto de la rugosidad en disipar calor sería más importante (Eviner and Chapin 2003;Adams 2007).…”
Section: D��������unclassified
“…The complete cutting of trees, however, removes the entire canopy and thus presumably would have the opposite effect. Indeed, a negative radiative forcing of up to −18 Wm −2 in summer was measured from clear-cutting in the temperate zone (Houspanossian et al, 2013).…”
Section: The Effects Of Forest Thinning On Summertime Albedomentioning
confidence: 99%